Strategi perbankan syariah dalam mendukung ekonomi inklusif di Indonesia - Radliyah, Diana Rahmah (Maliki Interdisciplinary Journal, 2024)
Islamic banking in Indonesia has a strategic role in supporting an inclusive economy through various innovations and approaches based on sharia principles. This study discusses three main strategies used by Islamic banking: digitization of services, increasing Islamic financial literacy, and strengthening financing for MSMEs. Digitalization, such as mobile banking and QRIS services, enables wider financial access, especially for people in remote areas. In addition, the Islamic financial literacy program run in conjunction with the Financial Services Authority (OJK) contributes to increasing public understanding of Islamic financial products, which encourages increased financial inclusion. On the other hand, MSME financing through sharia contracts such as mudharabah and musyarakah is the main focus to support small businesses in developing their businesses sustainably. With this approach, Islamic banking not only contributes to economic growth but also creates a fair and inclusive financial system. The conclusion of this study shows that Islamic banking has great potential in accelerating the achievement of an inclusive economy in Indonesia, in line with the government's efforts to create equal and equitable welfare.